2013
DOI: 10.1111/j.1464-410x.2012.11736.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of adding behavioural treatment or antimuscarinic drug therapy to α‐blocker therapy in men with nocturia

Abstract: • Nocturia is a common and bothersome lower urinary tract symptom, particularly in men. Many single drug therapies have limited benefit.• For men who have persistent nocturia despite alpha-blocker therapy, the addition of behavioural and exercise therapy is statistically superior to anticholinergic therapy. Objective• To compare reductions in nocturia resulting from adding either behavioural treatment or antimuscarinic drug therapy to a-adrenergic antagonist (a-blocker) therapy in men. Patients and Methods• Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 34 publications
(59 reference statements)
1
24
0
Order By: Relevance
“…Second, both the treatment groups received behavioral therapy, which is the first‐line management strategy for nocturia, while pharmacotherapy is an add‐on therapy in those with failed behavioral therapy. Behavioral therapy has been reported to have similar to better efficacy than pharmacotherapy in older women with incontinence, and men with OAB . Antimuscarinics with behavioral therapy may therefore adequately address nocturia due to urgency and excessive fluid load, in some patients, though in others it may not respond due to the multifactorial etiology of nocturia …”
Section: Discussionmentioning
confidence: 99%
“…Second, both the treatment groups received behavioral therapy, which is the first‐line management strategy for nocturia, while pharmacotherapy is an add‐on therapy in those with failed behavioral therapy. Behavioral therapy has been reported to have similar to better efficacy than pharmacotherapy in older women with incontinence, and men with OAB . Antimuscarinics with behavioral therapy may therefore adequately address nocturia due to urgency and excessive fluid load, in some patients, though in others it may not respond due to the multifactorial etiology of nocturia …”
Section: Discussionmentioning
confidence: 99%
“…Cochrane review published in 2014 supports the widespread recommendation that PFMT be included in first-line conservative management programs for women with stress and other types of urinary incontinence [21]. PFMT has evolved over decades, both as a behavioral therapy and a physical therapy, combining principles from behavioral science, nursing, and muscle physiology into a widely recommended conservative treatment [22] but before pharmacotherapy, BT including life style modifications and PFMT should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…These studies verify the exacerbating role of MetS-induced metabolic derangements in the development of BPE (4) . Investigating of uncomplicated lower urinary tract symptoms (LUTS) in men who used a self-management programme in addition to standard care or standard care alone demonstrated that behavioural treatment reduced nightly nocturia by a mean of 0.97 episodes and was significantly more effective than drug therapy (5) . However, all attention in alternative approach for BPH was usually associated with the phytotherapeutic agents, as natural products, containing inherently vast structural diversity than synthetic compounds, have been the major resources for discovering new drugs (6) .…”
Section: Introductionmentioning
confidence: 99%